2021
DOI: 10.3389/fpls.2021.653791
|View full text |Cite
|
Sign up to set email alerts
|

ThCOL2 Improves the Salt Stress Tolerance of Tamarix hispida

Abstract: The CONSTANS-LIKE (COL) transcription factor has been reported to play important roles in regulating plant flowering and the response to abiotic stress. To clone and screen COL genes with excellent salt tolerance from the woody halophyte Tamarix hispida, 8 ThCOL genes were identified in this study. The expression patterns of these genes under different abiotic stresses (high salt, osmotic, and heavy metal) and abscisic acid (ABA) treatment were detected using quantitative real-time PCR (qRT-PCR). The expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…There are similar reports that IAA significantly promotes the accumulation of POD enzymatic activities in potato ( Solanum tuberosum L.) and ground nutrients under salt stress [ 12 ]. The current results are consistent with previous reports, suggesting that increased antioxidant enzyme activity contributes to plant tolerance to stress [ 37 , 38 ]. However, with the addition of the auxin inhibitor NPA, the levels of photosynthetic pigments, ROS and enzyme activities in quinoa seedlings were not significantly different from those under salt stress, which further demonstrated that the regulation of antioxidant enzymatic and nonenzymatic systems during the maintenance of quinoa salt tolerance is dependent on IAA.…”
Section: Discussionsupporting
confidence: 94%
“…There are similar reports that IAA significantly promotes the accumulation of POD enzymatic activities in potato ( Solanum tuberosum L.) and ground nutrients under salt stress [ 12 ]. The current results are consistent with previous reports, suggesting that increased antioxidant enzyme activity contributes to plant tolerance to stress [ 37 , 38 ]. However, with the addition of the auxin inhibitor NPA, the levels of photosynthetic pigments, ROS and enzyme activities in quinoa seedlings were not significantly different from those under salt stress, which further demonstrated that the regulation of antioxidant enzymatic and nonenzymatic systems during the maintenance of quinoa salt tolerance is dependent on IAA.…”
Section: Discussionsupporting
confidence: 94%
“…For Arabidopsis transformation, the GmUGT gene was subcloned into pFGC5941 ( Lei et al, 2021 ) driven by the ATUGT72B1 promoter using the ClonExpress II One Step Cloning Kit (Vazyme, Nanjing, China); the clone, thus, prepared was introduced into the Arabidopsis atugt72b1 mutant with EHA105 by the floral dip method ( Clough and Bent, 1998 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, overexpression of Ghd2 in rice (Oryza sativa) significantly impairs drought resistance and plays a crucial role in drought-induced leaf senescence [154]. In the halophyte Tamarix hispida, ThCOL2 protein enhances the activity of protective enzymes, reduces ROS and MDA accumulation in plants, and mitigates cell damage to enhance salt tolerance in transgenic plants [155]. In maize (Zea mays), eight members of group I ZmCOL possess ABA-responsive cis-elements, and their expression levels are modulated by ABA, indicating their widespread involvement in ABA response [25].…”
Section: Col Participates In Abiotic Stress Responsementioning
confidence: 99%